Effects of Ground Fennel Seed Supplementation to diet on Some Blood and Liver Parameters in Quails - Filiz KAZAK; Tülay ÇİMRİN and Sema ALAŞAHAN (ISPEC Journal of Agricultural Sciences, 2020)
This study was carried out to determine the effects of ground fennel seed supplementation to quail rations on some blood parameters and liver oxidant-antioxidant parameters. In the study 32 Japanese quails (16 male + 16 female) were used. Four groups were formed as 8 animals in each group: control male and control female groups were fed a basal diet containing no feed additive; fennel male and fennel female groups were fed a basal diet with added 1% of ground fennel seed for a period of 28 days, ad libitum. It was determined that adding 1% ground fennel seed to the ration decreased liver MDA level and GPx activity and increased Vit C levels (P<0.05). Liver GSH and Vit C levels were higher in fennel male group compared to control male group (P<0.05). The liver GPx activity in the fennel female group was found to be lower compared to the control female group (P<0.001). Addition of fennel to the ration had no effect on serum CHOL, LDL, HDL levels, AST and ALT activities (P>0.05). The study showed that the supplementation of 1% ground fennel seeds to quail ration can affect the liver oxidant-antioxidant balance without altering serum total cholesterol, LDL, HDL levels, AST and ALT activities. In addition, it should be taken into account that serum and liver values in quails may differ depending on gender in such studies.